Early Strength Evolution of Cement Grouts Adopted in Reinforced Concrete Subjected to Na2SO4 Corrosion - Yinshan Xu; Jianqiang Zhou; Sujing Jin (Buildings, 2023)
Due to the harsh application environment, sodium sulfate corrosion poses a considerable threat to the performance of reinforced concrete. Considering high fluidization and early strength cement grouts (HECG) are widely adopted in the repair engineering of reinforced concrete, HECG are also subjected to the action of corrosive substances. Even though numerous research results disclosed the effect of sodium sulfate corrosion on the performance and the degradation mechanisms of conventional cement grouts, the degradation mechanisms of HECG under sodium sulfate corrosion are still to be studied because HECG have the exceptional characteristics of high fluidization and early strength that conventional cement grouts do not have. Hence, the compressive and flexural strengths of HECG after corrosion with different sodium sulfate solution concentrations and corrosion times were tested in this study. Moreover, the evolution of the microstructure of HECG in the process of corrosion was analyzed with a Scanning Electron Microscope (SEM) test. The changes in the hydration products were investigated through the X-ray diffraction (XRD) test and the Differential Scanning Calorimeter (DSC) test. Consequently, the degradation mechanisms of HECG in the case of different sodium sulfate solution concentrations and corrosion times were revealed. The results indicate that the corrosion of sodium sulfate and hydration exists simultaneously when the corrosion time is less than 7 days. When the corrosion time is 14 days, the hydration of HECG was complete. The main source of the early strength of HECG is that the C-S-H gel crosses and clings to form a solid and compact whole in three-dimensional space. The effect of Na2SO4 on the early strength formation of HECG is that the corrosion of Na2SO4 can postpone the conversion of CH crystal into C-S-H gel and damage the generated CH crystal. This study on the degradation mechanisms of HECG exposed to sodium sulfate corrosion can provide new ideas for sulfate resistance and durability design of HECG.